2014
DOI: 10.9790/0853-13355155
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Evaluation and Their Antibiotic Sensitivity Pattern in Tonsillitis

Abstract: The Study Was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 10 publications
5
16
2
1
Order By: Relevance
“…In the study by Agrawal et al on all age group patients, common causative organisms isolated from the tonsillar surface were alpha-hemolytic Streptococci, Staphylococcus aureus, non-pathogenic Neisseria species, Haemophilus influenza, Pneumococcus, Enterococcus, Bacteroid fragilis, and Corynebacterium species. No anaerobes were identified [ 8 ]. In another study by Omer et al in Turkey, an attempt was made to isolate the facultative and obligate anaerobes from the surface and core of patients with recurrent tonsillitis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Agrawal et al on all age group patients, common causative organisms isolated from the tonsillar surface were alpha-hemolytic Streptococci, Staphylococcus aureus, non-pathogenic Neisseria species, Haemophilus influenza, Pneumococcus, Enterococcus, Bacteroid fragilis, and Corynebacterium species. No anaerobes were identified [ 8 ]. In another study by Omer et al in Turkey, an attempt was made to isolate the facultative and obligate anaerobes from the surface and core of patients with recurrent tonsillitis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrary the BabaiwaU.F et al 13 showed identical organism in both surface and core in maximum number of patients. Abdelaziz.M.E et al 14 showed variation in 62.5% cases and similarity in 37.5% and Agarwal.A et al 15 showed variation in surface and core organisms in 63.63% and similarity in 36.3%. This study showed that gentamycin, amikacin and ampiclox should be the treatment of choice for gram positive organisms, ciprofloxacin and sparfloxacin for the gram negative organisms (Table:9).…”
Section: Discussionmentioning
confidence: 96%
“…In Salman Mutiullah Shaikh et al, 13 the most common organism was Streptococcus pneumoniae (86.56%) followed by Staphylococcus aureus (47.76%). Bista M et al 9 showed Streptococcus viridans and Streptococcus pneumoniae and in Agarwal A et al 14 Streptococcus viridans and Branhamella catarrhalis (71.13%). So majority of tonsil core culture studies identified Staph.…”
Section: Methodsmentioning
confidence: 97%